Irony and Metapoetics in Theocritus' Idyll 18. - Walker, Guy (Mnemosyne, 2021)
Although scholarship has identified multiple ironic elements throughout Theocritus' Idyll 18, his epithalamium for Helen, this paper offers a new perspective on Theocritus' ambiguity, his allusive puns, and his ironic comparisons that masquerade as generic hymeneal topoi. Additionally, the embedded aetiology of Helen's tree-cult has long eluded interpretation. This paper proposes a metapoetic reading for the plane-tree and its arboreal inscription. As a mise en abyme , it forms a metatextual link between the imagined internal reader and the external audience to reflect on the power of the author and the text over the reader.